2013
DOI: 10.1186/1741-7015-11-228
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral dichlorodiphenyltrichloroethane (DDT) exposure promotes epigenetic transgenerational inheritance of obesity

Abstract: BackgroundAncestral environmental exposures to a variety of environmental factors and toxicants have been shown to promote the epigenetic transgenerational inheritance of adult onset disease. The present work examined the potential transgenerational actions of the insecticide dichlorodiphenyltrichloroethane (DDT) on obesity and associated disease.MethodsOutbred gestating female rats were transiently exposed to a vehicle control or DDT and the F1 generation offspring bred to generate the F2 generation and F2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
328
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(341 citation statements)
references
References 76 publications
(151 reference statements)
7
328
0
6
Order By: Relevance
“…These results are in agreement with previous studies which also found transgenerational increases in susceptibility to ovarian diseases after exposure of F0 generation pregnant rats to vinclozolin [15] or DDT [16]. Experimental exposure of pregnant rats to other environmental toxicants such as jet fuel hydrocarbons, the plastics compounds bisphenol A (BPA) and phthalates, the pesticides permethrin and methoxychlor, and the industrial pollutant dioxin have also been shown to promote a transgenerational increase in ovarian disease [15,42].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are in agreement with previous studies which also found transgenerational increases in susceptibility to ovarian diseases after exposure of F0 generation pregnant rats to vinclozolin [15] or DDT [16]. Experimental exposure of pregnant rats to other environmental toxicants such as jet fuel hydrocarbons, the plastics compounds bisphenol A (BPA) and phthalates, the pesticides permethrin and methoxychlor, and the industrial pollutant dioxin have also been shown to promote a transgenerational increase in ovarian disease [15,42].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the ovarian granulosa cells from the antral follicles of 6-month-old F3 generation vinclozolin lineage rats showed transgenerational changes in gene expression and alterations in the pattern of DNA methylation compared to F3 generation control lineage rats [15]. Similarly, exposure of F0 generation pregnant rats to the insecticide DDT (dichlorodiphenyltrichloroethane) induced an epigenetic transgenerational increase in ovarian diseases in the F3 generation, which was comprized of primordial follicle loss and increased rates of ovarian cysts [16]. Ancestral exposure to DDT also induced transgenerational changes in F3 generation sperm DNA methylation patterns [16], but epigenetic changes in ovarian somatic cells such as granulosa cell have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, atrazine inhibits meiosis in mice, but also affects gene expression in ways that can be inherited through the germline in the next generation (Gely-Pernot et al, 2015). Similarly, DDT exposure can result in transgenerational effects (Skinner et al, 2013b, Kabasenche and Skinner, 2014, Song et al, 2014 and at least two fungicides can have transgenerational effects (Skinner, 2011, Skinner et al, 2013a. These observations create an even greater concern.…”
Section: C Transgenerational Effectsmentioning
confidence: 99%
“…Michael Skinner, who studies epigenetics at Washington State University in Pullman, has exposed pregnant rats to various environmental contaminants: most recently, the pesticide dichlorodiphenyltrichloroethane (DDT) 16 . Although the chemical had no effect on the weight of the rats' offspring, more than half of the rats' great grandchildren grew fat.…”
Section: Clean Slatementioning
confidence: 99%